2022
DOI: 10.2147/ijnrd.s351515
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of Sleep Quality and Excessive Daytime Sleepiness in Conventional Hemodialysis Population: A Single-Center Experience

Abstract: Sleep disturbances are common in patients with end-stage kidney disease on hemodialysis (hemodialysis population: HDP). Higher rates of primary sleep disorders, demographic characteristics, metabolic abnormalities, and the efficacy of treatment place HDP at higher risk. The pattern observed is delayed onset of sleep, frequent awakening episodes, insomnia, sleep apnoea, excessive daytime sleepiness, restless leg syndrome, abnormal limb movements, pain in limbs, confusion, and nightmares. Two commonly used subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Different tools capture different aspects of sleep disturbances, leading to variations in reported rates. Consistent with previous research [18,23], our study found no significant gender-based differences in sleep quality among HD patients, indicating consistent experiences of poor sleep quality between male and female patients. These findings align with prior studies exploring gender differences in sleep patterns among individuals with chronic illnesses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Different tools capture different aspects of sleep disturbances, leading to variations in reported rates. Consistent with previous research [18,23], our study found no significant gender-based differences in sleep quality among HD patients, indicating consistent experiences of poor sleep quality between male and female patients. These findings align with prior studies exploring gender differences in sleep patterns among individuals with chronic illnesses.…”
Section: Discussionsupporting
confidence: 92%
“…It assesses the severity of difficulties with sleep onset, maintenance, early morning awakening, sleep dissatisfaction, interference with daytime functioning, noticeability of sleep problems by others, and distress caused by lack of sleep over the past month using a 5-point Likert scale (0 = no difficulty, 4 = very severe problem). The total score ranges from 0 to 28 and categories of insomnia are as follows: no insomnia (0-7), sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). The ISI is available in three forms: patient, clinician, and significant other.…”
Section: Psychometric Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data also exists about its prevalence in general population. Methods employed ranged from questionnaires 5,6,810,1214,16,1821,24,25,2932,34,3840,42,44,47,48,51,52,55,56,59,60,63,64,67,7075,80,82,84,87,88,9097,99–104 , home testing to overnight sleep studies 34,49,51,52,55,5866,68,69,98,99 . In some studies, screening using questionnaires was done followed by polysomnography 10,26,48,51,52,59,64,99 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive daytime sleepiness (EDS) remained a symptom which was found in many studies and analysis for EDS was done. Studies reporting insomnia or insomnia like features , OSA 13,22,26,27, , RLS 10,15,19,25,28,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and excessive daytime sleepiness 11,17,40,59,60,67,72,80,88,[91][92][93][94][95][96][97][98][99][100][101][102][103][104] were analysed. The details of which are tabulated in Table 1.…”
Section: Search Strategymentioning
confidence: 99%